Analysis of Protein Phosphorylation Using Phos‐Tag Gels. (25th July 2018) - Nagy, Zoltan; Comer, Shane; Smolenski, Albert
Abstract: Phos‐tag gels are recent tools to dissect protein phosphorylation that operate by inducing a shift in the electrophoretic mobility of phosphorylated proteins compared to their nonphosphorylated counterparts. This article describes the preparation and electrophoresis of Zn 2+ ‐Phos‐tag gels along with electrotransfer of the separated phospho‐ and nonphosphoproteins onto a PVDF membrane using either wet‐tank or semidry transfer. We also discuss the theory behind the technology with critical parameters to keep in mind for its successful application. © 2018 by John Wiley & Sons, Inc.